Cellularized Bilayer Pullulan-Gelatin Hydrogel for Skin Regeneration - Nicholas, Mathew N. (Tissue Eng Part A, 2016)
Skin substitutes significantly reduce the morbidity and mortality of patients with burn injuries and chronic wounds. However, current skin substitutes have disadvantages related to high costs and inadequate skin regeneration due to highly inflammatory wounds. Thus, new skin substitutes are needed. By combining two polymers, pullulan, an inexpensive polysaccharide with antioxidant properties, and gelatin, a derivative of collagen with high water absorbency, we created a novel inexpensive hydrogel—named PG-1 for “pullulan-gelatin first generation hydrogel”—suitable for skin substitutes. After incorporating human fibroblasts and keratinocytes onto PG-1 using centrifugation over 5 days, we created a cellularized bilayer skin substitute. Cellularized PG-1 was compared to acellular PG-1 and no hydrogel (control) in vivo in a mouse excisional skin biopsy model using newly developed dome inserts to house the skin substitutes and prevent mouse skin contraction during wound healing. PG-1 had an average pore size of 61.69 μm with an ideal elastic modulus, swelling behavior, and biodegradability for use as a hydrogel for skin substitutes. Excellent skin cell viability, proliferation, differentiation, and morphology were visualized through live/dead assays, 5-bromo-2′-deoxyuridine proliferation assays, and confocal microscopy. Trichrome and immunohistochemical staining of excisional wounds treated with the cellularized skin substitute revealed thicker newly formed skin with a higher proportion of actively proliferating cells and incorporation of human cells compared to acellular PG-1 or control. Excisional wounds treated with acellular or cellularized hydrogels showed significantly less macrophage infiltration and increased angiogenesis 14 days post skin biopsy compared to control. These results show that PG-1 has ideal mechanical characteristics and allows ideal cellular characteristics. In vivo evidence suggests that cellularized PG-1 promotes skin regeneration and may help promote wound healing in highly inflammatory wounds, such as burns and chronic wounds.